PERCEPTION OF “STRESS” AND “STRESSORS”AMONG FIRST YEAR MEDICAL STUDENTS AND EFFECT OF INTERVENTION ON THEIR STRESS PERCEPTION - Aisha, Dr (Pakistan Armed Forces Medical Journal, 2020)
Objective: To explore perception of stress & stressors among first year medical students, with or without intervention. Study Design: Quasi-experimental study. Place and Duration of Study: Shaheed Mohtarma Benazir Bhutto Medical University (SMBBMU), Larkana and duration of the study was of eight months starting from Oct 2017. Methodology: All the first year medical students who were willing to participate and present in class and filled the post it notes and perceived stress scale-questionnaire completely were included in this study. These 240 students were randomly divided to two equal groups of 120 students in each; group I received intervention and thus labeled as intervention group, whereas group 2 included remaining half of students which did not receive any intervention (non-intervention group). The intervention was in form of a 2 days’ workshop on stress management. The contents of workshop were carefully selected in concordance with the identified stressors from response of students on the post-it-notes. Results: About 45% (109) were boys and 55% (131) were girls. Most common stressors identified were, time management (24.1%), lack of guidance from teacher regarding test/exam preparation (20.8%), failure to memorize and retain learned facts (19.1%), lack of peer support (12.5%), frequent test/exams (10.8%) long courses (8.3%) and conflict with teachers/friends (4.1%). Mean baseline perceived stress scale score in intervention group was 19.72 ± 6.04 where as in non-intervention group it was 19.27 ± 0.583. The difference of PSS scores before (baseline) and after intervention (delayed) was statistically significant (p-value <0.001) between two groups. Conclusion: We may conclude from our study findings that the moderate degree of stress is not uncommon among first year medical students and the stress-management intervention improves perception of stress by addressing the common stressors as identified by them.